Disease Concerns among Breast Cancer Patients at The National Center for Radiotherapy and Nuclear Medicine in Khartoum State - Ali, Soha Mohamed; Eltahir, Elrasheed Ismaeil (Journal of Educational and Psychological Sciences, 2021)
The study addressed the pathological fears among women with breast cancer at the National Center for Radiotherapy and Nuclear Medicine in Khartoum. Aiming to identify the general characteristic of the pathological fears among women with breast cancer at the Center and the differences in the pathological fears among women with breast cancer at the center. Where the researchers used the descriptive method with a sample size of 35 women with breast cancer were chosen by the intentional method at the Center، they applied the pathological fears scale on the patients، the data was analyzed، they reached for results including: The pathological fears among women with breast cancer at the Center are high. There are no statistically significant differences between the pathological fears among women with breast cancer at the Center according to the variable of social status. Psychological and social care must be provided to women with breast cancer. Educating the patient with breast cancer in the final stages of her illness and the difficulties she will face and developing guidance programs so that she can deal with the health and psychological changes and face them، especially in her last days.
Keywords: Fear; Pathological Fears; Infected; Breast Cancer